2003
DOI: 10.1029/2002jd002226
|View full text |Cite
|
Sign up to set email alerts
|

The mean physical and optical properties of regional haze dominated by biomass burning aerosol measured from the C‐130 aircraft during SAFARI 2000

Abstract: [1] Instrumentation on the Met Office C-130 aircraft measured aerosol physical and optical properties during the Southern African Regional Science Initiative (SAFARI 2000) in September 2002 while flying from Windhoek, Namibia. Filter measurements of aged regional haze suggest a ratio of apparent elemental carbon (EC a ) to organic carbon (OC) of 0.12 ± 0.02 and mass fractions of 5% EC a , 25% inorganic compounds, and 70% organic matter (OC plus associated elements). The submicron size distribution of aged reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
369
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 264 publications
(423 citation statements)
references
References 51 publications
48
369
6
Order By: Relevance
“…The smoke and pollution effect on cloud cover generates a radiative forcing at the top of atmosphere that is about half of today's aerosol effect or Ϫ6 W͞m 2 , and reduction of sunlight available for evaporation from the ocean by 7 W͞m 2 , thus dominating climate change in this region. This finding is in line with the observation of a global dimming of sunlight at the surface over the land in the last 50 years (48) of 10-20 W͞m 2 , taking into account the higher aerosol concentrations over the land, near the sources, than over the ocean (1,49). Recent papers show that the dimming effect reversed in the mid-1980s and a brightening resumed (39,50).…”
Section: Resultssupporting
confidence: 73%
See 3 more Smart Citations
“…The smoke and pollution effect on cloud cover generates a radiative forcing at the top of atmosphere that is about half of today's aerosol effect or Ϫ6 W͞m 2 , and reduction of sunlight available for evaporation from the ocean by 7 W͞m 2 , thus dominating climate change in this region. This finding is in line with the observation of a global dimming of sunlight at the surface over the land in the last 50 years (48) of 10-20 W͞m 2 , taking into account the higher aerosol concentrations over the land, near the sources, than over the ocean (1,49). Recent papers show that the dimming effect reversed in the mid-1980s and a brightening resumed (39,50).…”
Section: Resultssupporting
confidence: 73%
“…Further south, Haywood et al (1) observed that the stratiform clouds are detached from the overlaying smoke layer, with a vertical separation of a few hundred meters. A recent modeling study (18) showed that under such conditions the absorption of sunlight by the smoke alone can influence the underlying stratiform clouds even without physical interaction.…”
Section: Understanding the Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…This compares with values of 0.85-0.90 measured during the Southern African Regional Science Initiative (SAFARI-2000) (Eck et al, 2003;Haywood et al, 2003a;Leahy et al, 2007). In contrast, the dust aerosol was very weakly absorbing with single-scattering albedos of around 0.98 at 550 nm .…”
Section: Introductionmentioning
confidence: 63%